Spectrum Absorbency of Metamaterial Perfect Absorber - Md Ali, Siti Adlina; Abu, Maisarah; Zabri, Siti Normi (International Journal of Integrated Engineering, 2022)
A triple-band metamaterial perfect absorber was introduced. The single meta-pattern based on gold-bar shaped was designed on the 0.02Î» Taconic TLY-5. The gold-bar shaped was designed horizontal initially was then being rotated anti-clockwise from 0o to 90o to analyse and understand the variation of absorption spectrum. Dual band perfect metamaterial absorber was achieved at 45o. Then, the gold-bar shaped was slotted at both end to develop triple-band metamaterial perfect absorber. The slotted gold-bar shaped was evaluated three absorption peaks: 99.94%, 99.88% and 99.66% at 3.98 GHz, 4.81 GHz and 5.33 GHz, respectively. This however, shifted to the 3.96 GHz, 4.80 GHz and 5.33 GHz with absorbency 99.79%, 99.95% and 99.90% for the measured structure. Both simulated and measure results were achieved absorbency over 99% which was almost perfect absorption (â‰ˆ100%). These properties are expected to be used in practical applications such as satellite and radar communications transmission. These properties of the metamaterial absorber could increase the functionality of the metamaterial absorber to be used in any application especially in reducing radar cross section for stealth application.